Writing Kit Carson : Fallen Heroes in a Changing West - Johnson, Susan Lee (Book collections on Project MUSE., 2020)
"In this critical biography, Susan Lee Johnson braids together lives over time and space, telling tales of two white women who, in the 1960s, wrote books about the fabled frontiersman Christopher 'Kit' Carson: Quantrille McClung, a Denver librarian who compiled the Carson-Bent-Boggs Genealogy, and Kansas-born but Washington, D.C.- and Chicago-based Bernice Blackwelder, a singer on stage and radio, a CIA employee, and the author of Great Westerner: The Story of Kit Carson. In the 1970s, as once-celebrated figures like Carson were falling headlong from grace, these two amateur historians kept weaving stories of western white men, including those who married American Indian and Spanish Mexican women, just as Carson had wed Singing Grass, Making Out Road, and Josefa Jaramillo"--